Pengaruh Gaya Hidup, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Sepatu Converse” (Kasus pada Mahasiswa YKPN Yogyakarta) - Rahmad Mustary Moeda Silalahi; Retno Hartati (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
This study was conducted with the aim of analyzing the effect of lifestyle, price, and product quality on converse shoe purchase decisions in YKPN Yogyakarta students. This study uses quantitative methods. The type of data used in this study is primary data and secondary data. Primary data obtained based on the dissemination of questionnaires to 205 respondents and secondary data retrieved via text books, journals, and sources from the research-related internet. Samples are taken using purposive sampling. The data is analyzed with multiple linear regression analysis techniques. The findings obtained from the research are lifestyles have a significant positive effect on the decision to buy converse shoes in YKPN Yogyakarta students. The price did not have a significant effect on the decision to buy converse shoes in YKPN Yogyakarta students. Product quality has a significant positive effect on the decision to purchase converse shoes in YKPN Yogyakarta students. Adjusted R2 of 0.526 or 52.6% which means lifestyle, price, and product quality have an effect of 52.6% on dependent variables of purchasing decisions, while 47.4% are caused by another independent variable that is not yet in the independent variables studied.